Aseptic meningitis after intravenous immunoglobulin (IVIG) infusion in children with immune thrombocytopenic purpura (ITP) - A Tamaddoni (Babol University of Medical Sciences, 2001)
Objective: The most common cause of acute onset of bleeding in children is autoimmune thrombocytopenic purpura (ITP) that appears 1-4 weeks after viral infections with petechia, mucosal and gum bleeding. The cause of ITP is anti-platelet antibody IgG/IgM and one of the methods for its treatment is IVIG infusion. Case: The patient was a 11-year-old girl with purpura on her foot that were diffused on other parts of her body, especially on her high. At first time, by diagnosis ITP, the patient with a history of bleeding and arthritis in two stages with platelet counts 110000 and 72000 was treated with prednisone. When drugs were interrupted, complications replaced again. In second stage, she was hospitalized and treated with IVIG infusion (400 mg/kg/day). After 3 days with symptoms such as headache, vomiting, neck rigidity cast doubt on meningitis. Therefore, LP was done and CSF findings confirmed aseptic meningitis and using of antibiotics was recommended. Conclusion: IVIG infusion that is used for treatment of different diseases such as primary immunodeficiencies, infection in LBW infants and patients with CLL and ITP has different complications. Aseptic meningitis is one of the complications in patients who use this drug.